2009
DOI: 10.1002/mnfr.200800492
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 3‐hydroxy‐β‐damascone and related carotenoid‐derived aroma compounds as novel potent inducers of Nrf2‐mediated phase 2 response with concomitant anti‐inflammatory activity

Abstract: Structural comparison of apple constituents with known inducers of phase two cytoprotective enzymes led to the identification of 3-hydroxy-beta-damascone and related carotenoid derived aroma compounds as potent inducers of NAD(P)H:quinone reductase (QR) activity. Damascone-related compounds were found to be more potent inducers than ionone derivatives, with CD values (concentrations required to double the specific activity of QR in Hepa1c1c7 cell culture) in the range of 1.0-5.7 microM. QR induction by 3-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…These carbonyl compounds have diverse biological activities by reacting with sulfhydryl groups of target proteins. Various phytochemicals and medicines with an ␣ , ␤ -unsaturated carbonyl structure were reported to have biological activity such as anti-tumor, anti-viral, and anti-infl ammatory activities (42)(43)(44). In the present study, three oxidative metabolites of xanthophylls were found to suppress the NO production by mouse macrophage RAW 264 cells stimulated with LPS.…”
Section: Discussionmentioning
confidence: 49%
“…These carbonyl compounds have diverse biological activities by reacting with sulfhydryl groups of target proteins. Various phytochemicals and medicines with an ␣ , ␤ -unsaturated carbonyl structure were reported to have biological activity such as anti-tumor, anti-viral, and anti-infl ammatory activities (42)(43)(44). In the present study, three oxidative metabolites of xanthophylls were found to suppress the NO production by mouse macrophage RAW 264 cells stimulated with LPS.…”
Section: Discussionmentioning
confidence: 49%
“…For example, they can act as antioxidants or exhibit antimicrobial properties (reviewed by Goff and Klee, 2006). It was found that these compounds can both up-regulate the phase 2 cytoprotective enzymes and inhibit the induction of pro-inflammatory enzymes (Gerhäuser et al, 2009). It was found that these compounds can both up-regulate the phase 2 cytoprotective enzymes and inhibit the induction of pro-inflammatory enzymes (Gerhäuser et al, 2009).…”
Section: Section 4 Compositional and Nutritional Aspectsmentioning
confidence: 99%
“…Preliminary studies highlight the fact that the varied chemical natures of these compounds significantly influence their biological activities (Gerhäuser et al, 2009). Moreover, systematic studies are needed to elucidate the specific chemical properties of each species.…”
Section: Section 4 Compositional and Nutritional Aspectsmentioning
confidence: 99%
“…[16] Apart from their role as aroma impact compounds, several norisoprenoids (β-ionone, β-damascenone, and 3-hydroxy-β-damascone) show health-related properties, such as anticarcinogenic activity. [17,18] Pandan leaves are a promising source of natural colorant, as well as a natural flavor precursor. In this work, a general screening of norisoprenoids and carotenoids as their precursors was performed.…”
Section: Introductionmentioning
confidence: 99%